Formulation, characterization and in vivo evaluation of nanoemulsion for enhancing oral bioavailability of ibuprofen / Nurfazreen Anuar - Anuar, Nurfazreen (2015)
Ibuprofen, a phenyl propionic acid derivative, plays a significant role in the treatment of rheumatoid arthritis, osteoarthritis and related conditions. However, ibuprofen is practically insoluble in water and would not completely absorb in the gastrointestinal tract. Nanoemulsion carrier system was formulated in this study to improve oral absorption of ibuprofen. A ternary phase diagram was constructed to identify the optimal concentrations of oil, surfactant and co-surfactant. It was found that formulation containing 3% ibuprofen, 57% olive oil, 15% SE L-1695 and 25% glycerol showed the best nanoemulsion property with droplet size of 232.1 run, polydispersity index of 0.047 and zeta potential of -31.7 mV. A reversed-phase high performance liquid chromatographic (RP-HPLC) method has been developed for the quantification of ibuprofen in rat plasma. The proposed method was validated based on linearity, accuracy and precision. The percentage mean recovery was found to be 99.16%, while the percentage of relative standard deviation of within-day and between-day measurements were all less than 5%. Subsequently, in vivo oral absorption study was conducted to determine the oral bioavailability of ibuprofen in rat plasma after administration. Ibuprofen nanoemulsion and oil solution in rat plasma showed AVe values of 6670.10 ± 283.83 ug/mlh and 3060.32 ± 169.93 ug/ml-h respectively. The absorption of ibuprofen nanoemulsion showed an increased by 2-folds in contrast to the absorption value of the oil formulation. Meanwhile, both ibuprofen macroemulsion A and macroemulsion B showed an increase ofAVC values by almost 1.5-fold as compared to the oil formulation. Therefore, it is proved that nanoemulsion formulation achieves higher rate of ibuprofen absorption as compared to macroemulsions and oil formulations.